2019
DOI: 10.1101/860064
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Task rule and choice are reflected by layer-specific processing in rodent auditory cortical microcircuits

Abstract: The primary auditory cortex (A1) is an essential node in the integrative brain network that encodes the behavioral relevance of acoustic stimuli, predictions, and auditory-guided decision making. Previous studies have revealed task-related information being present at both the single-unit and population activity. However, its realization with respect to the cortical microcircuitry is less well understood. In this study, we used chronic, laminar current source density (CSD) analysis from the A1 of behaving Mong… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…Changes in both FR and encoding efficiency were most prominent in deep layer neurons. These findings extend several previous studies reporting larger effects of attention in infragranular LFP and multi-unit activity (O'Connell et al, 2014;Zempeltzi et al, 2020). These physiological outcomes are consistent with anatomical work suggesting top-down modulatory signals arrive primarily in the supragranular and infragranular layers (Felleman and Van Essen, 1991).…”
Section: Discussionsupporting
confidence: 91%
“…Changes in both FR and encoding efficiency were most prominent in deep layer neurons. These findings extend several previous studies reporting larger effects of attention in infragranular LFP and multi-unit activity (O'Connell et al, 2014;Zempeltzi et al, 2020). These physiological outcomes are consistent with anatomical work suggesting top-down modulatory signals arrive primarily in the supragranular and infragranular layers (Felleman and Van Essen, 1991).…”
Section: Discussionsupporting
confidence: 91%
“…The probabilities are mapped by the inverse logit function (sigmoid): which restricts the model predictions to the interval [0, 1]. Because of these properties, a logistic regression with GLMs is well suited to compare data (and thus, evaluate predictions of ensuing vocal-output) on a single-trial basis 76 .…”
Section: Methodsmentioning
confidence: 99%
“…the relative pre-vocal power change). This value is dimensionless and independent of sample size 76, 77 , which makes it ideal to compare effect sizes of different models (e.g. across channels and frequency bands, as in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, electrical events during sensory responses were much slower than dendritic spikes. While some studies found the cross-laminar propagation of CSD components during cortical sensory responses (Jellema et al, 2004), CSD profiles of sensory response in most studies had laminar sinks/sources that remained within laminae without crossing over (Lakatos et al, 2007;Fishman and Steinschneider, 2010;Szymanski et al, 2011;Godlove et al, 2014;van Kerkoerle et al, 2014;Dougherty et al, 2017;Senzai et al, 2019;Zempeltzi et al, 2020).…”
Section: Traveling Activity or Electrical Conduction?mentioning
confidence: 98%